Service Quality Strategy in Increasing User Satisfaction of Beauty Clinic Services from a Legal Perspective in Indonesia - Jafan fifaldi Harahap; Andry Syafrizal Tanjung (International Journal of Society and Law, 2024)
This research aims to identify and analyze service quality strategies that can increase user satisfaction of beauty clinic services from a legal perspective in Indonesia. Beauty clinics as providers of health and beauty services have a responsibility to ensure that the services provided are not only effective and safe, but also comply with applicable regulations and legal standards. The research method used in this research is normative legal research, which involves analysis of library materials or secondary data. Even though there are regulations such as Law Number 29 of 2004 concerning Medical Practices and the Consumer Protection Law, their implementation still faces various challenges. This research underlines the importance of increasing the competency of medical and non-medical personnel through training and certification, the use of quality technology and products that meet national standards, as well as transparency of information and consumer education. In addition, improving responsive customer service and promoting ethical principles in medical practice were also identified as important factors in increasing service user satisfaction and trust. Through these strategies, beauty clinics can improve the quality of their services, ensure legal compliance, and ultimately increase consumer satisfaction and protection. This research provides concrete recommendations for beauty clinic practices in Indonesia so that they can operate to higher standards and provide greater benefits for consumers.